Servicios de bienestar universitario en el cread Bogotá: Servicio de acompañamiento psicologico (2020)
This article responds to the proposal to offer the psychological support service to the Cread Bogotá students; the objective is to preserve psychological well-being, optimize the coping of academic problems, and reduce risk factors in dropping out and permanence. The instrument used was a survey distributed in 30 questions, designed to characterize the population. 156 students belonging to the Schools of Humanistic Sciences and Education, Technological Sciences and Administrative and Economic Sciences participated. The proposed psychological service “Talk to me ... your online psychologist”, offers a personalized and virtual attention, deve- loping attention, promotion and prevention activities, as well as actions aimed at strengthening academic performance, autonomous learning and reducing attrition. In addition to an 8-week virtual course to reduce academic stress and strengthen autonomous learning consciously and intentionally from the Mindfulness strategy, which will allow the student not only strengthen their academic performance, but the skills for life.